Stereoselective Synthesis of cis-2,5-Disubstituted Pyrrolidines via Wacker-Type Aerobic Oxidative Cyclization of Alkenes with (t)Bu-Sulfinamide Nucleophiles - Redford, Joanne E. (2012)
[Image: see text] Palladium(II)-catalyzed aerobic oxidative cyclization of alkenes with tethered tert-butanesulfinamides furnishes enantiopure 2,5-disubstituted pyrrolidines, originating from readily available and easily diversified starting materials. These reactions are the first reported examples of metal-catalyzed addition of sulfinamide nucleophiles to alkenes.